Implementasi Sistem Kontrol Manajemen Energi Hibrid Berbasis Mikrokontroller - Muliawati, Fithri; Riyadi, Slamet; Annisa, Sarah Chairul; Afrianto, Yuggo; Ginting, Novita Br (PROtek : Jurnal Ilmiah Teknik Elektro, 2022)
Currently, world researchers are competing to find the most effective and efficient way to use renewable energy sources, namely energy from sunlight and solar and wind heat or it can be called hybrid energy. The use of this hybrid energy technology can certainly save conventional fuel and reduce the risk of ecosystem damage caused. This study aims to see the energy value resulting from the implementation of a hybrid energy management control system that has been created based on a microcontroller. With the experimental method, the results were obtained that the solar cell voltage value was highest at 11 pm with 28.87 Vdc, then for the voltage of the wind energy was the highest at 27.85 at the 3rd minute at 4 pm. For energy testing of batteries, the results were obtained that if there is only one energy source to charge the battery, it takes 9 hours while if it is a hybrid energy source, it only takes 2.5 hours. This proves that hybrid energy is very effective rather than relying solely on one of the energy sources.